The Beauties of the Use of Light and Color in Cinema: explores the film (Titanic) - DANA MOHAMMED ABDULLA; ZHILWAN TAHIR BAPIR (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study, titled The Beauties of the Use of Light and Color in Cinema, explores the film Titanic as an example. It is a descriptive and analytical study focusing on the artistic and scientific use of light and color in cinema. Light and color are vital elements that play a significant role in conveying the film's purpose and message to the audience. Through the strategic use of imagery, light, and color, viewers can discern the film's genre, whether it is tragic, comedic, romantic, social, or emotional. The study consists of four sections. The first section addresses the research methodology, including the research problem, significance, objectives, and limitations. The second section provides the theoretical framework, divided into four themes: the value of light and color in social life, the symbols of light and color, the role of light and color in cinema, and the dramatic effects of light and color. The third section focuses on the research application, detailing the research community, methodology, tools, and examples, with an analysis of the film Titanic, written and directed by James Cameron. Finally, the fourth section presents the results, recommendations, and a list of references.